PENERAPAN METODE DISKUSI MELALUI MEDIA TORSO TERHADAP KEAKTIFAN DAN HASIL BELAJAR BIOLOGI PADA SISWA KELAS XI IPA SMA NEGERI 2 SORONG - Sibarani, Anita Eliana; Antoh, Alfred A. (Jurnal Ilmu Pendidikan Indonesia, 2014)
This Research aims to analyse the applying of method of discussion study of through media torso to liveliness and result of learning biology class of XI IPA SMA Negeri 2 Kota Sorong. Metode used in this research is method of quasi experimental by sampel as much 92 one who divisible in 2 class (class kontrol and experiment). Result of research lay open that there are liveliness difference and result of learning student between class using discussionmethod of through media torso with the class using conventional method. For the difference of result of learning proved with the value Asymp. Sig (2-tailed) yielded by equal to 0,000 from test of Mann Whitney U. while for the liveliness of learn provable with the liveliness percentage by 5 accurate aspect, that is Visual activities equal to 73,90%, Oral Activities equal to 71,38%, Listening Activities equal to 73,90, Oral Activities equal to 71,38%, Listening Activities equal to 61,95%, writing activities wqual to 70,93% and bounce the activities equal to 71,74%. Keywords: Cooperative, NHT (Number Head Together), Microsoft Powerpoint.